Examining the Use of Social Media in Building a Student Personal Brand and the Impact of Demographics - Girard, Tulay; Pinar, Musa (Journal of Marketing Development and Competitiveness, 2021)
Personal branding has recently gained interest as employer requirements and recruitment practices have been transformed with advancements in technology. Social media platforms have made personal branding efforts both easy and challenging. Prior research pointed out that college students and graduates entering the job market need to understand the importance of current technology tools and utilize them in building their personal brand and searching for jobs. However, empirical research on the topic is very limited. To respond to this void, this study examines students’ perceptions of their efforts for building their personal brands using social media. Data were collected using an online survey at two universities in the U.S. The findings reveal that students’ perceptions of their efforts in building their personal brands differ by their use of social media platforms and demographics. Practical implications are discussed.